Luminescence landscapes of nitrogen-vacancy centers in diamond: quasi-localized vibrational resonances and selective coupling. Issue 26 (14th June 2019) - Su, Zhicheng; Ren, Zeyang; Bao, Yitian; Lao, Xiangzhou; Zhang, Jinfeng; Zhang, Jincheng; Zhu, Deliang; Lu, Youming; Hao, Yue; Xu, Shijie
Abstract : 77 K micro-photoluminescence spectrum, room-temperature near-field photoluminescence image, and a local atomic arrangement of the nitrogen-vacancy (NV) center in diamond. Abstract : Among the known color centers of diamond, the nitrogen-vacancy (NV) center composed of a substitutional nitrogen and its nearest carbon vacancy could be the most promising photon emitter. In this work, we present the micro-photoluminescence (μ-PL) landscapes of two quasi-localized vibrational resonances (∼45 and ∼63 meV) associated with the neutral (NV 0 ) and negative (NV − ) NV centers, respectively. A symmetric electron–phonon coupling theoretical model was used to simulate the μ-PL spectra with vibronic structures, so that the effective phonon densities of states and Huang–Rhys factors could be obtained for the two charge states of the NV centers. Our study also reveals that the perfect lattice optical phonon mode plays a more significant role in the luminescence of the NV 0 state, whereas the quasi-localized vibrational resonance plays the dominant role in the case of NV − . These new results may deepen the existing understanding of the luminescence properties of the NV centers in diamond.